Strengthening Concern for the School Environment through Open Space Greening Activities - Maria Assumpta Wikantari; Diah Nurdiana; Maria Jashinta Elisabet Hamboer; Puspa Rini (Journal Of Human And Education (JAHE), 2023)
The purpose of this article is to examine the effectiveness of environmental education in schools and its impact on students' understanding and engagement in environmental conservation. By analysing various educational programmes and their outcomes, the study aims to provide insight into how schools can better equip students with the knowledge and skills needed to protect natural resources. This research methodology involves a combination of quantitative and qualitative research methods. A sample of students from various grade levels and several teachers were selected and given pre- and post-tests to measure their critical thinking skills before and after participating in the PKM programme on strengthening awareness of the school environment through open space greening activities. The results of the study, namely: 1) in terms of student concern for the school environment, it is known that students and teachers are involved in greening school open spaces; and 2) The study found a positive correlation between good student and teacher habits, such as disposing of garbage in its place and caring for greenery in open school spaces.